FACTOR ANALYSIS OF ROTTER’S INTERPERSONAL TRUST SCALE - Pangalila, Sonya Amelia Christin; Budiarto, Yohanes (Universitas Ahmad Dahlan, 2017)
The aim of this study was to investigate the dimensions of Interpersonal Trust Scale using Exploratory Factor Analysis and Confirmatory Factor Analysis in emerging adulthood sample. Convenience sampling used as sampling technique for EFA (N=320) and CFA (N=485). Four dimensions identified by EFA were Exploitation Institutional Factor reflecting one’s trust to an institution and also caution to exploitative condition; Role Trust reflects one’s trust to certain figure in performing their social role; Sincerity measures one’s trust that others are sincere and honest; and Trust of the Future reflects one’s trust about something that has not happened. This factor solution was cross-validated using CFA and obtain two remaining, namely Caution dan Sincerity. Reliability of this scale is inadequate for practical purpose and might be useful to use other technique for reliability testing instead of internal consistency. AbstrakPenelitian ini bertujuan untuk mengetahui dimensi-dimensi yang terdapat pada alat ukur Interpersonal Trust Scale menggunakan metode Exploratory Factor Analysis dan Confirmatory Factor Analysis pada dewasa awal. Convenience sampling digunakan sebagai teknik pengambilan sampel untk EFA (N=320) dan CFA (485). EFA menghasilkan empat dimensi yaitu Exploitation Institutional Factor merupakan faktor yang menunjukkan tingkat kepercayaan seseorang terhadap suatu institusi serta mengandung butir yang menunjukkan kewaspadaan orang terhadap situasi eksploitatif; Role Trust menunjukkan tingkat kepercayaan terhadap figur tertentu dalam menjalankan peran sosial; Sincerity berisikan butir yang menujukkan kepercayaan bahwa orang lain tulus dan jujur dalam berperilaku; dan Trust of the Future berisikan butir yang menunjukkan kepercayaan seseorang terhadap sesuatu yang belum terjadi. Faktor yang diperoleh dari hasil analisis EFA diuji menggunakan CFA dan memeroleh dua faktor yang tersisa yaitu Caution dan Sincerity. Reliabilitas yang cukup rendah menunjukkan diperlukannya uji reliabilitas yang lain.